cpCST: a new continuous performance test for high-precision assessment of attention across the lifespan - MacKay-Brandt, Anna; Garcia-Barnett, Daniel; Gan, Kai Xuan; Ripley, Olivia; Gazes, Elaine; Milham, Michael; Colcombe, Stan (Frontiers in Psychology, 2025)
IntroductionAssessing sustained attention presents methodological challenges, particularly when spanning diverse populations whose baseline sensorimotor functioning may vary significantly.MethodsThis study introduces the Continuous Performance Critical Stability Task (cpCST), a novel paradigm combining high-density sampling of behavior (30 Hz), individualized calibration, and fixed-difficulty assessment to measure attentional control. In a sample of 166 adults (ages 18–76), we evaluated the psychometric properties of the cpCST’s instantaneous reaction time (iRT) metric derived through dynamic time warping.ResultsThe cpCST demonstrated exceptional reliability (bootstrap split-half r = 0.999) and predictive validity for cognitive performance (flanker and Woodcock-Johnson) and cardiorespiratory fitness (VO2submax). The task achieved high temporal efficiency, with just 2 min of data correlating at r = 0.94 with full-task performance, outperforming a standard arrow-based flanker task. The cpCST’s individualized calibration effectively isolated attentional control processes from baseline sensorimotor function, eliminating age-related slowing effects typically observed in reaction time tasks.DiscussionThis approach offers methodological advantages for lifespan studies, clinical populations, integration with neurophysiological measures, and computational modeling approaches while addressing limitations of existing attention assessment paradigms.